Long term monitoring of the reproductive behavior of wild Chinese pangolin (Manis pentadactyla) - Nick Ching-Min Sun (Nature Portfolio, 2021)
Abstract Observations of Chinese pangolin (Manis pentadactyla) in the wild are extremely rare and challenging because of their nocturnal and cryptic activity patterns and low population density. The present article reported the first field observation in eastern Taiwan, from October 4, 2012 to June 16, 2016, on the reproductive behavior of the Chinese pangolin based on the monitoring of a female (LF28) using radiotelemetry and camera traps. During this period, LF28 aged from 1–4.5 years old and gave two single-births, both took place in early December, at 3 and 4 years old, respectively. We recorded the entire 157 days of the first nursing period from parturition to maternal separation. For the second infant, the gestation period was estimated to be around 150 days based on the evidence that the pregnancy started in early Jul. 2015 and the offspring was born on Dec. 9, 2015. During the entire nursing period, LF28 frequently moved the offspring from one nursing burrow to another staying various durations ranging from 1 day to more than 35 days, and almost all (= 15/16) of these burrows were located in the core (MCP75) of LF28’s home range. Started from the month of parturition and lasting throughout the whole nursing period, different adult males constantly visiting the nursing burrows were recorded. Mating behavior was recorded once outside the burrow in March, which provided evidence of the occurrence of post-partum estrus in this species. Delayed implantation was proposed based on the observation of a several months lag between copulation and the estimated pregnancy initiation date. The present study demonstrated the advantage of using remote technologies to learn the life history of resting fossorial species.